DATA TAK BERSAMBUT: PERSEPSI KEPALA SEKOLAH DASAR ATAS SINERGI KEBIJAKAN RAPOR PENDIDIKAN - Ayu Pratiwi, Diani; Sulisitiyana; Suriansyah, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of Indonesia's national education system through the implementation of the Education Report Card represents a major shift towards data-driven evaluation practices. However, the extent to which elementary school principals are able to interpret, utilize, and respond to this policy has not been widely studied. This study aims to examine the perceptions of elementary school principals towards the policy synergy between the central government and local governments in the implementation of the Education Report Card. Using a descriptive quantitative approach, this study involved 85 elementary school principals in Banjarmasin City from a total of 260 questionnaires distributed. The instrument used was a structured Likert scale questionnaire that assessed five main dimensions: personal readiness, quality of school management, utilization of the education report card, condition of facilities and infrastructure, and perceptions of policy synergy. The results of the study indicate that although principals have high personal readiness and positive perceptions of the national evaluation policy, there are still challenges in its implementation, especially related to limited facilities, minimal support from local governments, and low institutional data literacy. This study concludes that policy implementation is not enough just through data dissemination, but must be accompanied by ongoing cross-government collaboration, contextual capacity building, and comprehensive systemic support. These findings provide a basis for improving policy design and encourage further longitudinal and mixed-method studies to evaluate the long-term impact of report card-based school improvement strategies.